The teaching of modern foreign languages in the primary school - Driscoll, P.; Frost, D. (b)
It has been argued for some time that to improve language learning in Britain we need to start earlier, as many other European countries do. This book is addressed to policy makers and teachers who are considering the possibility of getting involved in the teaching of MFL in the primary school.
Includes references and index.
Keywords: Electronic books; EDUCATION Elementary; Languages, Modern Study and teaching (Elementary).